The Effect of Whispering Game Toward Students’ Vocabulary Mastery at First Grade MTsN 1 Agam - Octaviani, Feby; Melani, Melyann; Reflinda, Reflinda; Roza, Veni (Pusdikra-Publishing.com, 2024)
Vocabulary is an essential aspect of acquiring four English language skills. However, many students found some difficulties, such as students had low vocabulary mastery, students had a limited number of vocabulary, and students had psychological barriers to learning vocabulary. Therefore, the goal of the study was to determine whether using whispering games had any impact on students' ability to master language. A quasi-experimental design and quantitative methods were used in this study. Then, the population of study was a student of the first grade, MTsN 1 Agam. The study applied purposive sampling and pre- and post-test test were used in the study. The experimental class and the control class would be given the pre- test and post-test, and the researchers would compare the means of the two groups using independent sample t-tests. The calculation's findings indicate that the t-count value is higher than the t-table value. The degree of freedom at a significance level of 0.05 is 57 (14.313>0.05). With these findings, null hypothesis can be rejected. It indicates that first-grade MTsN 1 Agam vocabulary mastery achieved through whispering games is better than conventional techniques.